Pore water geochemistry at two seismogenic areas in the Sea of Marmara. (2nd July 2015) - Ruffine, Livio; Germain, Yoan; Polonia, Alina; de Prunelé, Alexis; Croguennec, Claire; Donval, Jean‐Pierre; Pitel‐Roudaut, Mathilde; Ponzevera, Emmanuel; Caprais, Jean‐Claude; Brandily, Christophe; Grall, Céline; Bollinger, Claire; et al.
Abstract Within the Sea of Marmara, the highly active North Anatolian Fault (NAF) is responsible for major earthquakes (Mw ≥ 7), and acts as a pathway for fluid migration from deep sources to the seafloor. This work reports on pore water geochemistry from three sediment cores collected in the Gulfs of Izmit and Gemlik, along the Northern and the Middle strands of the NAF, respectively. The resulting data set shows that anaerobic oxidation of methane (AOM) is the major process responsible for sulfate depletion in the shallow sediment. In the Gulf of Gemlik, depth concentration profiles of both sulfate and alkalinity exhibit a kink‐type profile. The Sulfate Methane Transition Zone (SMTZ) is located at moderate depth in the area. In the Gulf of Izmit, the low concentrations observed near the seawater‐sediment interface for sulfate, calcium, strontium, and magnesium result from rapid geochemical processes, AOM, and carbonate precipitation, occurring in the uppermost part of the sedimentary column and sustained by free methane accumulation. Barite dissolution and carbonate recrystallization have also been identified at deeper depth at the easternmost basin of the Gulf of Izmit. This is supported by the profile of the strontium isotope ratios (87Sr/86Sr) as a function of depth which exhibits negative anomalies compared to the modern seawater value. The strontium isotopic signature also shows that these carbonates had precipitated during the reconnection of the Sea of Marmara with the Mediterranean Sea. Finally, a first attempt to interpret the sulfate profiles observed in the light of the seismic activity at both sites is presented. We propose the hypothesis that seismic activity in the areas is responsible for the transient sulfate profile, and that the very shallow SMTZ depths observed in the Gulf of Izmit is likely due to episodic release of significant amount of methane.